A molybdenum disulfide / manganese-mof / nitrogen-doped carbon nanosheet composite electrode and a preparation method thereof
Patent Information
- Application Number
- CN202611106599.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-09
AI Technical Summary
但目前MoS2/MOF复合材料的制备仍面临诸多技术挑战:一方面,现有方法多采用一步水热法同时生成MoS2和MOF,由于二者结晶温度差异显著(MoS2通常需180–220℃,而多数MOF在高于160℃时结构易坍塌),难以实现两相的可控同步生长,导致界面结合不紧密或相分离;另一方面,部分制备方法采用物理混合或层层自组装方式,所得材料界面接触电阻大,且需要额外的粘结剂将粉体催化剂固定于电极表面,易引入额外界面阻抗并掩盖活性位点,降低电子传输效率
1、本发明采用两步水热分段构筑策略,第一步高温(200℃)水热实现MoS2纳米片的充分晶化与垂直生长,第二步低温(150℃)水热实现Mn基MOF的原位生长而不破坏下层MoS2结构。该分步策略避免了两相结晶温度不匹配导致的结构坍塌或相分离问题,使MOF纳米颗粒紧密锚定于MoS2表面形成清晰异质结界面,有效促进界面电子转移并产生协同催化效应。
Smart Images

Figure CN122879756A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrocatalytic materials technology, and in particular to a MoS2 / Mn-MOF@NF composite electrode and its preparation method. Background Technology
[0002] Hydrogen, with its high energy density (120 MJ / kg), environmental friendliness, and renewability, is considered one of the important energy carriers for replacing fossil fuels in the future. Among various hydrogen production technologies, water electrolysis is widely regarded as a promising approach due to its relatively mild process conditions, lower equipment requirements, and high product purity. However, in the water electrolysis process, the hydrogen evolution reaction (HER) at the cathode typically exhibits a high overpotential, significantly increasing energy consumption and thus raising the cost of hydrogen production.
[0003] Currently, the catalysts that can effectively reduce the overpotential of the hydrogen evolution reaction in commercial applications are mainly the noble metal platinum and its compounds. However, the limited reserves and high prices of platinum group metals make it difficult to meet the needs of large-scale application of water electrolysis for hydrogen production, severely restricting its further promotion. Therefore, developing non-noble metal hydrogen evolution catalysts that are abundant, low-cost, and have excellent performance has become an important research direction in the field of electrocatalysis. Among non-noble metal hydrogen evolution catalysts, molybdenum disulfide (MoS2) has attracted much attention due to its unique layered structure, tunable phase composition, and excellent chemical stability. Theoretical studies have shown that the edge sites of MoS2 have high hydrogen adsorption Gibbs free energy, which can simulate the catalytic behavior of the noble metal platinum, thus providing effective reactive sites for the hydrogen evolution reaction. However, bulk MoS2 has catalytic inertness and poor conductivity on its basal surface, and nano-sized MoS2 is prone to agglomeration during preparation, resulting in insufficient exposure of active sites and limiting the full realization of its intrinsic catalytic activity. In addition, metal-organic frameworks (MOFs) also show great promise in the field of electrocatalysis due to their ultra-high specific surface area, tunable pore structure, and abundant metal active centers. However, most MOF materials have low intrinsic conductivity, insufficient electrochemical stability in strong base or strong acid electrolytes, and large charge transport resistance when used directly as electrode materials, making it difficult to achieve ideal hydrogen evolution performance when used alone.
[0004] Existing technologies indicate that constructing heterostructures by combining MoS2 and MOF materials can leverage interfacial electronic interactions to regulate the electronic structure of active sites, achieving synergistic catalytic effects and potentially overcoming the performance limitations of single materials. However, the preparation of MoS2 / MOF composites still faces numerous technical challenges: Firstly, existing methods often employ a one-step hydrothermal approach to simultaneously generate MoS2 and MOF. Due to the significant difference in their crystallization temperatures (MoS2 typically requires 180–220℃, while most MOFs are prone to structural collapse above 160℃), it is difficult to achieve controllable synchronous growth of the two phases, resulting in weak interfacial bonding or phase separation. Secondly, some preparation methods employ physical mixing or layer-by-layer self-assembly, leading to high interfacial contact resistance and requiring additional binders to fix the powdered catalyst to the electrode surface. This can introduce additional interfacial impedance and mask active sites, reducing electron transport efficiency. Furthermore, in existing technologies, the surface of MoS2 readily generates an inactive molybdenum oxide phase during synthesis, and the lack of effective in-situ reduction control methods further limits the overall catalytic activity of the composite material. Summary of the Invention
[0005] In view of the above situation, the main objective of this invention is to provide a MoS2 / Mn-MOF@NF composite electrode and its preparation method to solve the above-mentioned technical problems.
[0006] This invention proposes a method for preparing a MoS2 / Mn-MOF@NF composite electrode, the method comprising the following steps: Step 1: Pre-treat the nickel foam to obtain pre-treated nickel foam; Step 2: Mix sodium molybdate, thioacetamide, urea, dimethylformamide, graphene ethanol dispersion and ultrapure water, and dissolve them completely by magnetic stirring to prepare precursor solution A; Step 3: The pretreated nickel foam is placed in precursor solution A, and an inert gas is introduced to remove air before the first hydrothermal reaction is carried out, so that MoS2 nanosheets and graphene are grown in situ on the surface of the nickel foam. After cooling, washing and drying, MoS2-loaded nickel foam is obtained. Step 4: Place the MoS2-loaded nickel foam in an ice bath of sodium hydroxide solution and add sodium borohydride for chemical reduction treatment to remove molybdenum oxide on the surface of the nickel foam and increase sulfur vacancies. After washing and drying, reduced MoS2-loaded nickel foam is obtained. Step 5: Mix 2,5-dihydroxyterephthalic acid, manganese chloride, dimethylformamide and methanol, and stir magnetically until fully dissolved to prepare precursor solution B; Step 6: Place the reduced state of MoS2-loaded nickel foam in precursor solution B, and introduce an inert gas to remove air before carrying out the second hydrothermal reaction, so that Mn-based MOF grows in situ on the surface of MoS2 to form a heterostructure. After cooling, washing and drying, the nickel foam-loaded MoS2 / MOF composite material is obtained. The nickel foam-loaded MoS2 / MOF composite material is used as the MoS2 / Mn-MOF@NF composite electrode.
[0007] The present invention also proposes a MoS2 / Mn-MOF@NF composite electrode, wherein the MoS2 / Mn-MOF@NF composite electrode uses nickel foam as a carrier, MoS2 nanosheets are grown in situ vertically on the surface of nickel foam to form a first catalytic layer, and Mn-based MOF nanoparticles are grown in situ on the surface of MoS2 to form a second catalytic layer. The first catalytic layer and the second catalytic layer form a heterojunction interface, and the graphene is uniformly distributed between the MoS2 layers to form a three-dimensional conductive network.
[0008] Beneficial effects: 1. This invention employs a two-step hydrothermal segmented construction strategy. The first step involves high-temperature (200℃) hydrothermal treatment to achieve full crystallization and vertical growth of MoS2 nanosheets. The second step involves low-temperature (150℃) hydrothermal treatment to achieve in-situ growth of Mn-based MOFs without damaging the underlying MoS2 structure. This step-by-step strategy avoids structural collapse or phase separation problems caused by temperature mismatch between the two phases, allowing MOF nanoparticles to be tightly anchored on the MoS2 surface to form a clear heterojunction interface, effectively promoting interfacial electron transfer and generating a synergistic catalytic effect.
[0009] 2. By introducing sodium borohydride ice bath reduction treatment between two hydrothermal steps, the inactive molybdenum oxide phase on the surface of MoS2 can be selectively removed under mild conditions. Simultaneously, sulfur vacancy defects are introduced into the crystal lattice, adjusting the electronic structure of the Mo center and optimizing the hydrogen adsorption free energy (ΔG_H). This reduction treatment can also increase the surface roughness and wettability of the material, exposing more edge active sites, thereby significantly improving intrinsic catalytic activity.
[0010] 3. By introducing a graphene-ethanol dispersion in the first hydrothermal step, graphene sheets are uniformly distributed between MoS2 nanosheets, constructing a three-dimensional conductive network. This structure not only compensates for the poor intrinsic conductivity of MoS2 and accelerates charge transfer from the nickel substrate to the catalytic active sites, but also acts as a physical support to prevent the aggregation of MoS2 nanosheets, enhancing the structural stability of the electrode.
[0011] 4. This invention utilizes an in-situ growth strategy to sequentially construct a MoS2 and MOF dual-active layer on the surface of conductive nickel foam, forming a self-supporting composite electrode structure. This structure eliminates the need for additional binders, avoiding the problems of binders obscuring active sites and increasing interfacial impedance in traditional powder catalyst coating processes. Simultaneously, the nickel foam acts as a three-dimensional conductive framework, providing continuous electron transport channels and forming a tight mechanical bond with the catalyst layer, ensuring that the catalyst layer does not detach during long-term electrolysis at high current densities.
[0012] 5. The introduction of Mn-based MOF (Mn-MOF-74) not only provides abundant metal active centers, but its open pore structure also facilitates electrolyte penetration and rapid desorption of hydrogen bubbles, reducing mass transfer resistance. Furthermore, the heterogeneous interface between MoS2 and MOF generates an electronic rearrangement effect, which can optimize the adsorption energy of reaction intermediates, reduce the kinetic energy barrier of hydrogen evolution reaction, and exhibit a smaller Tafel slope.
[0013] 6. The entire synthesis process of this invention adopts conventional hydrothermal reaction, without the need for high-temperature calcination or complex atmosphere control. The reaction conditions are mild, the equipment requirements are low and the reproducibility is good. The raw material system is simple and does not require expensive template agents. It has good process scalability and batch preparation potential, and is suitable for the large-scale preparation of high-performance self-supporting composite electrode materials in the field of water electrolysis for hydrogen production.
[0014] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by means of embodiments of the invention. Attached Figure Description
[0015] Figure 1 This section describes the surface morphology characterization of the catalyst after the first and second hydrothermal steps in embodiments of the present invention; wherein, in Figure 1 In the image, 'a' represents a low-magnification SEM image of MoS2@NF; Figure 1 In the image, b represents a high-magnification SEM image of MoS2@NF; Figure 1 In the image, 'c' represents a low-magnification SEM image of Mn-MOF / MoS2@NF; Figure 1 In the image, d represents a high-magnification SEM image of Mn-MOF / MoS2@NF; Figure 2 These are XRD phase analysis diagrams of representative catalysts in the embodiments and comparative examples of the present invention; wherein, in Figure 2 In this context, 'a' represents MoS2@NF; Figure 2 In this context, b represents Mn-MOF / MoS2@NF; Figure 2 In this context, c represents Mn-MOF / MoS2@NF (2 times the amount of sulfur source, comparative example 7); Figure 3 Characterization of the hydrogen evolution electrochemical performance of catalysts with different MOF loadings in the embodiments and comparative examples of the present invention; wherein, in Figure 3 In the figure, 'a' represents the LSV curves of samples with different MOF loadings (0.25, 0.5, 1, and 2 times); Figure 3 In this context, 'b' represents the corresponding Tafel slope curve. Figure 4 The hydrogen evolution electrochemical performance of the catalysts prepared at different hydrothermal reaction temperatures in the first step of the embodiments and comparative examples of the present invention was characterized; wherein, in Figure 4 In the figure, 'a' represents the LSV curves of samples at different temperatures (180℃, 200℃, 220℃); Figure 4 In this context, 'b' represents the corresponding Tafel slope curve. Figure 5 Characterization of the hydrogen evolution electrochemical performance of catalysts prepared at different hydrothermal reaction temperatures in the second step of the embodiments and comparative examples of the present invention; wherein, in Figure 5 In the figure, 'a' represents the LSV curves of samples at different temperatures (140℃, 150℃, 160℃); Figure 5 In this context, 'b' represents the corresponding Tafel slope curve. Figure 6 The electrochemical performance characterization of hydrogen evolution is shown in the comparison of key process steps in the embodiments and comparative examples of this invention; wherein, in Figure 6 In the figure, 'a' represents the LSV curve of the key comparative examples (one-step hydrothermal method, no reduction, no graphene addition, pure MoS2, pure Mn-MOF, and Example 1); Figure 6 In this context, 'b' represents the corresponding Tafel slope curve. Figure 7 Characterization of the hydrogen evolution electrochemical performance of catalysts prepared with different amounts of thioacetamide in the embodiments and comparative examples of the present invention; wherein, in Figure 7 In the figure, 'a' represents the LSV curves of samples with different sulfur source concentrations (0.5x, 1x, 1.5x, 2x); Figure 7 In this context, 'b' represents the corresponding Tafel slope curve. Figure 8 The catalyst of Example 1 at 10 mA cm -2 Chronopotential (CP) test curve under constant current density for 20 hours. Detailed Implementation
[0016] Embodiments of the present invention are described in detail below. Examples of these embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0017] These and other aspects of the embodiments of the present invention will become clear from the following description and accompanying drawings. In these descriptions and drawings, some specific embodiments of the present invention are specifically disclosed to illustrate some ways of implementing the principles of the embodiments of the present invention; however, it should be understood that the scope of the embodiments of the present invention is not limited thereto.
[0018] Example 1: This embodiment 1 provides a method for preparing a nickel-based MoS2 / Mn-MOF composite electrode, the method comprising the following steps: Step 1: Pre-treat the nickel foam to obtain pre-treated nickel foam. The pre-treatment of nickel foam includes: ultrasonic cleaning with deionized water and anhydrous ethanol for 3 min each, followed by ultrasonic acid washing with 1 mol / L hydrochloric acid solution for 5 min, ultrasonic cleaning with methanol and acetone for 5 min each, and finally immersion in anhydrous ethanol for preservation to prevent oxidation, thus obtaining pre-treated nickel foam.
[0019] Step 2: Take 0.0225g sodium molybdate, 0.0225g thioacetamide, 0.045g urea, 5mL dimethylformamide, 240μL graphene dispersion with a concentration of 0.4g / L, and 50mL ultrapure water, and stir magnetically for 30min to fully dissolve them to prepare precursor solution A.
[0020] Step 3: Place the pretreated nickel foam in precursor solution A, and purge with argon gas for 3 minutes to remove air. Then, carry out the first hydrothermal reaction at 180°C for 16 hours to allow MoS2 nanosheets and graphene to grow in situ on the surface of the nickel foam. After cooling, washing and drying, obtain MoS2-loaded nickel foam, denoted as A1. The washing process involves washing twice with deionized water and twice with anhydrous ethanol, with each washing lasting 3 minutes.
[0021] Step 4: Place the MoS2-loaded nickel foam in A1 in a 0.005 mol·L⁻¹ container. -1 The nickel foam was chemically reduced for 20 min by adding 0.04 g of sodium borohydride to a 20 mL sodium hydroxide solution in an ice bath to remove molybdenum oxide from the surface of the nickel foam and increase sulfur vacancies. After washing and drying, reduced nickel foam loaded with MoS2 was obtained, denoted as B1. The washing was performed twice with deionized water and twice with anhydrous ethanol, each time for 3 min.
[0022] Step 5: Mix 19.2 mg of 2,5-dihydroxyterephthalic acid, 18.3 mg of manganese chloride, 15.95 mL of dimethylformamide and 1.45 mL of methanol, and stir magnetically for 15 min to fully dissolve them to prepare precursor solution B.
[0023] Step 6: Place the reduced MoS2-loaded nickel foam in B1 into precursor solution B, and purge with argon gas for 3 minutes to remove air. Then, carry out the second hydrothermal reaction at 140℃ for 20 hours to allow Mn-based MOF to grow in situ on the MoS2 surface to form a heterostructure. After cooling, washing, and drying, obtain the nickel foam-loaded MoS2 / MOF composite material. Use the nickel foam-loaded MoS2 / MOF composite material as the MoS2 / Mn-MOF@NF composite electrode, denoted as C1. The washing process involves washing twice with deionized water and twice with anhydrous ethanol, with each washing time being 3 minutes.
[0024] Example 2: This embodiment 2 provides a method for preparing a nickel-based MoS2 / Mn-MOF composite electrode, the method comprising the following steps: Step 1: Pre-treat the nickel foam to obtain pre-treated nickel foam. The pre-treatment of nickel foam includes: ultrasonic cleaning with deionized water and anhydrous ethanol for 3 min each, followed by ultrasonic acid washing with 1 mol / L hydrochloric acid solution for 5 min, ultrasonic cleaning with methanol and acetone for 5 min each, and finally immersion in anhydrous ethanol for preservation to prevent oxidation, thus obtaining pre-treated nickel foam.
[0025] Step 2: Take 0.0225g sodium molybdate, 0.045g thioacetamide, 0.05g urea, 5mL dimethylformamide, 240μL graphene dispersion with a concentration of 0.5g / L, and 60mL ultrapure water, and stir magnetically for 30min to fully dissolve them to prepare precursor solution A.
[0026] Step 3: Place the pretreated nickel foam in precursor solution A, and purge with nitrogen for 4 minutes to remove air. Then, carry out the first hydrothermal reaction at 200°C for 20 hours to allow MoS2 nanosheets and graphene to grow in situ on the surface of the nickel foam. After cooling, washing and drying, obtain MoS2-loaded nickel foam, denoted as MoS2@NF. The washing process involves washing twice with deionized water and twice with anhydrous ethanol, with each washing lasting 3 minutes.
[0027] Step 4: Place the MoS2-loaded nickel foam in a 0.01 mol·L⁻¹ container. -1 The nickel foam was chemically reduced for 30 min by adding 0.05 g of sodium borohydride to a 20 mL sodium hydroxide solution in an ice bath to remove molybdenum oxide from the surface of the nickel foam and increase sulfur vacancies. After washing and drying, reduced nickel foam loaded with MoS2 was obtained, denoted as R-MoS2@NF. The washing was performed twice with deionized water and twice with anhydrous ethanol, each time for 3 min.
[0028] Step 5: Mix 19.2 mg of 2,5-dihydroxyterephthalic acid, 20.8 mg of manganese chloride, 17.25 mL of dimethylformamide and 1.45 mL of methanol, and stir magnetically for 15 min to fully dissolve them to prepare precursor solution B.
[0029] Step 6: Place the reduced MoS2-loaded nickel foam in precursor solution B, and purge with nitrogen for 4 minutes to remove air. Then, carry out the second hydrothermal reaction at 150°C for 24 hours to allow Mn-based MOF to grow in situ on the MoS2 surface to form a heterostructure. After cooling, washing, and drying, obtain the nickel foam-loaded MoS2 / MOF composite material. Use the nickel foam-loaded MoS2 / MOF composite material as the MoS2 / Mn-MOF@NF composite electrode, denoted as Mn-MOF / MoS2@NF. The washing process involves washing twice with deionized water and twice with anhydrous ethanol, with each washing lasting 3 minutes.
[0030] Example 3: This embodiment 3 provides a method for preparing a nickel-based MoS2 / Mn-MOF composite electrode, the method comprising the following steps: Step 1: Pre-treat the nickel foam to obtain pre-treated nickel foam. The pre-treatment of nickel foam includes: ultrasonic cleaning with deionized water and anhydrous ethanol for 3 min each, followed by ultrasonic acid washing with 1 mol / L hydrochloric acid solution for 5 min, ultrasonic cleaning with methanol and acetone for 5 min each, and finally immersion in anhydrous ethanol for preservation to prevent oxidation, thus obtaining pre-treated nickel foam.
[0031] Step 2: Take 0.0225g sodium molybdate, 0.0675g thioacetamide, 0.054g urea, 5mL dimethylformamide, 240μL graphene dispersion with a concentration of 0.6g / L, and 75mL ultrapure water, and stir magnetically for 30min to fully dissolve them to prepare precursor solution A.
[0032] Step 3: Place the pretreated nickel foam in precursor solution A, and purge with argon gas for 5 minutes to remove air. Then, carry out the first hydrothermal reaction at 220°C for 24 hours to allow MoS2 nanosheets and graphene to grow in situ on the surface of the nickel foam. After cooling, washing and drying, obtain MoS2-loaded nickel foam, denoted as A3. The washing is performed twice with deionized water and twice with anhydrous ethanol, each time for 3 minutes.
[0033] Step 4: Place the MoS2-loaded nickel foam in A3 in a 0.02 mol·L⁻¹ container. -1The nickel foam was chemically reduced for 40 min by adding 0.06 g of sodium borohydride to a 20 mL sodium hydroxide solution in an ice bath to remove molybdenum oxide from the surface of the nickel foam and increase sulfur vacancies. After washing and drying, reduced nickel foam loaded with MoS2 was obtained, denoted as B3. The washing was performed twice with deionized water and twice with anhydrous ethanol, each time for 3 min.
[0034] Step 5: Mix 19.2 mg of 2,5-dihydroxyterephthalic acid, 36.6 mg of manganese chloride, 18.85 mL of dimethylformamide and 1.45 mL of methanol, and stir magnetically for 15 min to fully dissolve them to prepare precursor solution B.
[0035] Step 6: Place the reduced MoS2-loaded nickel foam in B3 into precursor solution B, and purge with argon gas for 5 minutes to remove air. Then, carry out the second hydrothermal reaction at 160℃ for 28 hours to allow Mn-based MOF to grow in situ on the MoS2 surface to form a heterostructure. After cooling, washing, and drying, obtain the nickel foam-loaded MoS2 / MOF composite material. Use the nickel foam-loaded MoS2 / MOF composite material as the MoS2 / Mn-MOF@NF composite electrode, denoted as C3. The washing process involves washing twice with deionized water and twice with anhydrous ethanol, with each washing time being 3 minutes.
[0036] Example 4: The difference between Example 4 and Example 2 is that the hydrothermal temperature in the second step of step 6 is 140°C, while the other conditions are the same as in Example 2. The resulting product is denoted as Mn-MOF / MoS2@NF-4.
[0037] Example 5: The difference between Example 5 and Example 2 is that the hydrothermal temperature in the second step of step 6 is 160°C, while other conditions are the same as in Example 2. The resulting product is denoted as Mn-MOF / MoS2@NF-5.
[0038] Example 6: The difference between Example 6 and Example 2 is that in step 5, the amount of 2,5-dihydroxyterephthalic acid is 4.8 mg, and the amount of manganese chloride is 5.2 mg. Other conditions are the same as in Example 2. The resulting product is denoted as Mn. 0.25 -MOF / MoS2@NF.
[0039] Example 7: The difference between Example 7 and Example 2 is that in step 5, the amount of 2,5-dihydroxyterephthalic acid is 9.6 mg, and the amount of manganese chloride is 10.4 mg. Other conditions are the same as in Example 2. The resulting product is denoted as Mn. 0.5 -MOF / MoS2@NF.
[0040] Example 8: The difference between Example 8 and Example 2 is that the amount of thioacetamide used in step 2 is 0.015g, while other conditions are the same as in Example 2. The resulting product is denoted as Mn-MOF / MoS2@NF-8.
[0041] Example 9: The difference between Example 8 and Example 2 is that the amount of thioacetamide used in step 2 is 0.0675g, while other conditions are the same as in Example 2. The resulting product is denoted as Mn-MOF / MoS2@NF-9.
[0042] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that steps 2 to 6 are combined, all raw materials are added at the same time, and the next step is hydrothermal at 200°C for 24 hours, without intermediate reduction steps.
[0043] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step 4, sodium borohydride reduction, is omitted, and the second hydrothermal step is performed directly after the first hydrothermal step.
[0044] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that no graphene ethanol dispersion was added in step 2.
[0045] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that step 5, which involves preparing the precursor solution B, and step 6, which involves the second hydrothermal step, are omitted. The final product is obtained after step 4.
[0046] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that step 2, which involves preparing precursor solution A, and step 3, which involves the first hydrothermal treatment, are omitted. The pretreated nickel foam is directly processed through steps 4 to 6.
[0047] Comparative Example 6: The difference between Comparative Example 6 and Example 2 is that the amount of 2,5-dihydroxyterephthalic acid used in step 5 is 38.4 mg, and the amount of manganese chloride is 41.6 mg (twice the standard amount).
[0048] Comparative Example 7: The difference between Comparative Example 7 and Example 2 is that the amount of thioacetamide used in step 2 is 0.090g (twice the standard amount).
[0049] Application Example 1: This embodiment proposes an application of a nickel-based MoS2 / Mn-MOF composite electrode, which is used for the electrocatalytic hydrogen evolution reaction. As a working electrode, the nickel-based MoS2 / Mn-MOF composite electrode exhibits excellent hydrogen evolution catalytic activity and stability in alkaline electrolyte.
[0050] To verify the effectiveness of the present invention, the electrochemical performance of Examples 2 and Comparative Examples 1-7 was tested in 1.0M KOH electrolyte; the reference electrode was a mercury / mercury oxide electrode (Hg / HgO), the counter electrode was a graphite rod, and the LSV scan rate was 5 mV s. -1 .
[0051] This invention tested the effect of the first step hydrothermal temperature on the crystallization of MoS2 and the performance of the composite catalyst, please refer to Table 1; Table 1: Effect of the first-step hydrothermal temperature on the crystallization of MoS2 and the performance of the composite catalyst;
[0052] From Table 1 and Appendix Figure 4 It can be seen that 200 ℃ is the optimal temperature for the first step of hydrothermal treatment. At 180 ℃ (Example 1), MoS2 crystallization is incomplete, the nanosheets are thin and have poor vertical orientation; at 220 ℃ (Example 3), although the crystallinity is further improved, the excessive thickness of the sheets leads to a reduction in the exposure of edge active sites, which in turn reduces the catalytic activity.
[0053] The present invention also tested the impact of key process steps on hydrogen evolution performance, and the test results are shown in Table 2 below; Table 2: Impact of key process steps on hydrogen evolution performance;
[0054] From Table 2 and Appendix Figure 6 The test results show that Example 2 (complete two-step method + reduction + graphene) exhibits the best hydrogen evolution kinetic performance, with a Tafel slope of only 18.1 mV dec. -1 In the one-step hydrothermal method (Comparative Example 1), due to temperature conflicts leading to MOF decomposition or incomplete MoS2 crystallization, the Tafel slope reached as high as 73.8 mV dec. -1 The sample without graphene (Comparative Example 3) lacked a three-dimensional conductive network, resulting in hindered charge transport and an increased Tafel slope of 10⁹ mV dec. -1 This demonstrates the necessity of graphene.
[0055] This invention tested the effect of the second-step hydrothermal temperature on hydrogen evolution performance; the test results are shown in Table 3 below. Table 3: Effect of hydrothermal temperature in the second step on hydrogen evolution performance;
[0056] From Table 3 and Appendix Figure 5It can be seen that 150℃ is the optimal temperature for the second hydrothermal step. At 140℃ (Example 2), MOF crystallization is insufficient and the heterojunction interface is not fully constructed; at 160℃ (Example 3), although MOF crystallization is improved, it may damage the underlying MoS2 structure or lead to excessive MOF growth.
[0057] This invention tested the effect of MOF loading on hydrogen evolution performance; the test results are shown in Table 4 below. Table 4: Effect of MOF loading on hydrogen evolution performance;
[0058] From Table 4 and Appendix Figure 3 It can be seen that the MOF loading exhibits an inverted U-shaped relationship. The synergistic effect is best when the loading is 25.6 mg (Example 1); the active sites are insufficient when the loading is 6.4 mg and 12.8 mg (Examples 6 and 7); when the loading is 51.2 mg (Comparative Example 6), the MOF layer is too thick, blocking the pores and masking the active sites in the lower layer.
[0059] This invention tests the effect of thioacetamide dosage on hydrogen evolution performance; the test results are shown in Table 5 below. Table 5: Effect of thioacetamide dosage on hydrogen evolution performance;
[0060] From Table 5 and Appendix Figure 7 It can be seen that there is an optimal window for the dosage of thioacetamide. When the dosage is 0.0225g (Example 1), the MoS2 crystals are complete and the sulfur vacancy concentration is suitable; when the dosage is too low (Example 8), the crystallization is incomplete; when the dosage is too high (Example 9, Comparative Example 7), the number of MoS2 layers grows excessively, the in-plane sulfur saturation leads to a decrease in conductivity, and the Tafel slope increases significantly.
[0061] exist Figure 1 In the study, scanning electron microscopy (SEM) characterization results showed that after the first hydrothermal reaction, MoS2 nanosheets grew in a vertical orientation on the surface of nickel foam (in... Figure 1 In the middle of a, in Figure 1 In step b), the Mn-MOF nanoparticles are uniformly thick with clear edges, forming an open two-dimensional nanoarray structure, which is beneficial for electrolyte penetration and exposure of active sites. After the second step of low-temperature hydrothermal reaction, the Mn-MOF nanoparticles are uniformly anchored on the surface of the MoS2 nanosheets (in... Figure 1 In the c of the middle, in Figure 1 In the d-phase, the particles are uniform in size, densely distributed, and without agglomeration. The two phases are in close contact, forming a clear MoS2 / MOF heterojunction bilayer structure.
[0062] exist Figure 2X-ray diffraction (XRD) phase analysis showed that the first-step hydrothermal product MoS2@NF ( Figure 2 The material exhibits distinct 2H-MoS2 characteristic diffraction peaks, corresponding to crystal planes (002), (100), and (110), indicating good crystallinity. The final composite material of Example 1 (… Figure 2 Besides retaining the characteristic peak of MoS2, no molybdenum oxide impurities such as MoO3 or MoO2 were detected, proving that sodium borohydride ice bath reduction treatment effectively removed the inactive surface oxide phase. Comparative Example 7 (2 times the amount of sulfur source, Figure 2 Although no molybdenum oxide impurities were present, the MoS2(002) peak intensity was significantly enhanced and the peak position shifted to a lower angle, indicating excessive layer growth and intensified in-plane stacking. Figure 7 This is consistent with the electrochemical results showing a significant increase in the Tafel slope.
[0063] In summary, Embodiment 2 of this invention effectively solves the problem of phase separation or structural collapse caused by the temperature mismatch between MoS2 and MOF by adopting a two-step hydrothermal segmented construction strategy (the first step is to achieve in-situ vertical growth of MoS2 nanosheets and graphene through high-temperature hydrothermal treatment at 200℃, and the second step is to achieve tight anchoring of Mn-MOF nanoparticles through low-temperature hydrothermal treatment at 150℃). Through intermediate sodium borohydride ice bath reduction treatment, the inactive molybdenum oxide phase on the surface of MoS2 is selectively removed and sulfur vacancy defects are introduced, which significantly optimizes the electronic structure of active sites. Through the construction of a three-dimensional conductive network of graphene, the insufficient intrinsic conductivity of MoS2 is compensated for and the charge transport is accelerated.
[0064] The synergistic innovation of the above-mentioned technical solutions distinguishes this invention from the single-material and simple composite strategies in existing technologies. Figure 6 As shown in Table 2, in Comparative Example 1 (one-step hydrothermal method), due to temperature conflicts, MOF decomposition or incomplete MoS2 crystallization occurred, resulting in an overpotential as high as 220 mV and a Tafel slope of 73.8 mV dec. -1 Comparative Example 2 (without intermediate reduction) showed an overpotential of 78 mV due to residual molybdenum oxide and the absence of sulfur vacancies on the surface; Comparative Example 3 (without graphene) showed an overpotential of 150 mV and a Tafel slope as high as 109 mV due to the lack of a three-dimensional conductive network and the resulting hindered charge transport. -1 Comparative Examples 4 (simple MoS2@NF) and 5 (simple Mn-MOF@NF) exhibited overpotentials of 95 mV and 105 mV, respectively, due to the lack of heterojunction synergy and conductive framework support. In contrast, Example 1 (complete process) showed an overpotential of only 65 mV and a Tafel slope as low as 18.1 mV dec. -1 and at 10mA cm -2 During a 20-hour stability test, the current retention rate was maintained at >95% (in Figure 8The invention fully demonstrates its significant advantages in hydrogen evolution catalytic activity, kinetic rate, and long-term stability.
[0065] Therefore, this invention successfully constructed a self-supporting nickel-based MoS2 / Mn-MOF composite electrode with a tight heterojunction interface through stepwise in-situ growth, interfacial chemical reduction regulation, and synergistic optimization of conductive networks, providing a high-performance, low-cost, and simple catalytic material preparation scheme for the field of water electrolysis for hydrogen production.
[0066] In the description of this specification, references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0067] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.
Claims
1. A method for preparing a MoS2 / Mn-MOF@NF composite electrode, characterized in that, The method includes the following steps: Step 1: Pre-treat the nickel foam to obtain pre-treated nickel foam; Step 2: Mix sodium molybdate, thioacetamide, urea, dimethylformamide, graphene ethanol dispersion and ultrapure water, and dissolve them completely by magnetic stirring to prepare precursor solution A; Step 3: The pretreated nickel foam is placed in precursor solution A, and an inert gas is introduced to remove air before the first hydrothermal reaction is carried out, so that MoS2 nanosheets and graphene are grown in situ on the surface of the nickel foam. After cooling, washing and drying, MoS2-loaded nickel foam is obtained. Step 4: Place the MoS2-loaded nickel foam in an ice bath of sodium hydroxide solution and add sodium borohydride for chemical reduction treatment to remove molybdenum oxide on the surface of the nickel foam and increase sulfur vacancies. After washing and drying, reduced MoS2-loaded nickel foam is obtained. Step 5: Mix 2,5-dihydroxyterephthalic acid, manganese chloride, dimethylformamide and methanol, and stir magnetically until fully dissolved to prepare precursor solution B; Step 6: Place the reduced state of MoS2-loaded nickel foam in precursor solution B, and introduce an inert gas to remove air before carrying out the second hydrothermal reaction, so that Mn-based MOF grows in situ on the surface of MoS2 to form a heterostructure. After cooling, washing and drying, the nickel foam-loaded MoS2 / MOF composite material is obtained. The nickel foam-loaded MoS2 / MOF composite material is used as the MoS2 / Mn-MOF@NF composite electrode.
2. The method for preparing the MoS2 / Mn-MOF@NF composite electrode according to claim 1, characterized in that, In step 1, the pretreatment of the nickel foam includes: The nickel foam was ultrasonically cleaned for 3 minutes each with deionized water and anhydrous ethanol, then ultrasonically acid-washed for 5 minutes with 1 mol / L hydrochloric acid solution, then ultrasonically cleaned for 5 minutes each with methanol and acetone, and finally soaked in anhydrous ethanol for preservation to prevent oxidation, thus obtaining the pretreated nickel foam.
3. The method for preparing the MoS2 / Mn-MOF@NF composite electrode according to claim 1, characterized in that, In step 2, the mass of sodium molybdate is 0.0225 g, the mass of thioacetamide is 0.0225-0.0675 g, the mass of urea is 0.045-0.054 g, the mass of dimethylformamide is 5 mL, the volume of graphene ethanol dispersion is 240 μL, the concentration of graphene ethanol dispersion is 0.4-0.6 g / L, the volume of ultrapure water is 50-75 mL, and the magnetic stirring time is 30 min.
4. The method for preparing the MoS2 / Mn-MOF@NF composite electrode according to claim 1, characterized in that, In step 3, the inert gas introduced is argon or nitrogen, and the gas introduction time is 3-5 minutes. In the first step of the hydrothermal reaction, the reaction temperature is 180-220℃ and the reaction time is 16-24h; The washing process involved washing twice with deionized water and twice with anhydrous ethanol, with each washing session lasting 3 minutes.
5. The method for preparing the MoS2 / Mn-MOF@NF composite electrode according to claim 1, characterized in that, In step 4, the volume of the sodium hydroxide solution is 20 mL, and the concentration of the sodium hydroxide solution is 0.005-0.02 mol·L⁻¹. -1 The amount of sodium borohydride added is 0.04-0.06 g per 20 mL of sodium hydroxide solution; the chemical reduction treatment time is 20-40 min. The washing process involved washing twice with deionized water and twice with anhydrous ethanol, with each washing session lasting 3 minutes.
6. The method for preparing the MoS2 / Mn-MOF@NF composite electrode according to claim 1, characterized in that, In step 5, the mass of 2,5-dihydroxyterephthalic acid is 19.2 mg, the mass of manganese chloride is 18.3-36.6 mg, the volume of dimethylformamide is 15.95-18.85 mL, the volume of methanol is 1.45 mL, and the magnetic stirring time is 15 min.
7. The method for preparing the MoS2 / Mn-MOF@NF composite electrode according to claim 1, characterized in that, In step 6, the inert gas introduced is argon or nitrogen, and the gas introduction time is 3-5 minutes. The hydrothermal reaction temperature in the second step is 140-160℃, and the reaction time is 20-28 hours. The washing process involved washing twice with deionized water and twice with anhydrous ethanol, with each washing session lasting 3 minutes.
8. A MoS2 / Mn-MOF@NF composite electrode, characterized in that, The MoS2 / Mn-MOF@NF composite electrode is prepared using the method described in any one of claims 1-7.
9. The MoS2 / Mn-MOF@NF composite electrode according to claim 8, characterized in that, The MoS2 / Mn-MOF@NF composite electrode uses nickel foam as a carrier. MoS2 nanosheets are grown in situ vertically on the surface of nickel foam to form a first catalytic layer, and Mn-based MOF nanoparticles are grown in situ on the surface of MoS2 to form a second catalytic layer. The first catalytic layer and the second catalytic layer form a heterojunction interface. The graphene is uniformly distributed between the MoS2 layers to form a three-dimensional conductive network.